PENCEGAHAN FRAUD DI PEMERINTAH DESA - Provita Wijayanti; Rustam Hanafi (Jurnal Akuntansi Multiparadigma, 2018)
Abstract: The Fraud Prevention in Village Government. The purpose of this study is to examine the effect of a number of variables related to individuals and culture on fraud tendencies. The method used is multiple dummy regression analysis with 40 village apparatuses in Sayung sub-district, Demak as samples. The main finding of this study is that the cultivation of individual morality in a good village government can prevent fraud. This can be done through guidance to village officials, such as increasing faith and piety, gratitude, patience, and increasing self-righteousness.